A needs assessment for bachelors in rehabilitation in several provinces in the Central and Highlands of Vietnam - Nguyen, Thi Van Kieu; Ngo, Van Dong; Vinh, Khanh; Vo, Ngoc Ha My; Nguyen, Thi Mai Anh; Nguyen, Thi Bao Ngoc; Pham, Thi Thu Ha; Ho, Uyen Phuong; Hoang, The Hiep; Nguyen, Thanh Gia; Le, Dinh Duong; Nguyen, Minh Tu (Tạp chí Y Dược Huế, 2024)
Background: The study aims to describe the training need of bachelor’s degree holders in rehabilitation, providing insights for the University of Medicine and Pharmacy, Hue University, to structure training programs in fields that align with societal demands. Materials and method: A cross-sectional study, data was collected through telephone interviews using a semi-structured questionnaire with hospital leaders regarding the demand for rehabilitation professionals in 30 hospitals in 8 provinces in the Central and Highlands regions. Results: There are a total of 89 rehabilitation therapists with university degrees, and they are unevenly distributed among the specialties. Specifically, rehabilitation therapists who specialize in physical therapy occupied more than half of the total workforce (53.4%), while the proportion of orthotists is the lowest at 9.2%. Furthermore, 90% of hospitals in the Central and Highlands regions express the training need of bachelor’s degree holders in rehabilitation therapy (considering it necessary or very necessary). Conclusions: The number of rehabilitation therapists in the Central and Highlands regions remains low, and there is an unequal distribution of human resources among different specialties. Most hospitals require the training of bachelor’s degree holders in rehabilitation.